Interdisciplinary Science Man and Machines Student Document - Raine Derek; Scott Jon; Abel Paul (The University of Hull)
Man and Machines covers topics from the fields of biophysics and physiology - you will research in depth the structure and function of some of the systems of the human body from biological, biochemical and physical perspectives.